Warehouses financing: short on logic and long on imagination - Pavaskar, Madhoo (2006)
The attempt by the RBI to promote warehouse financing for agricultural commodities is undoubtedly a welcome move. The major problem, however, is that the country lacks modern warehouses. It would have been much better if the RBI - constituted Working on Warehouse Receipts and Commodity Futures had drawn up a road map to develop the warehouse receipt system for bank financing against agricultural commodities. - Reproduced.
Keywords: Agricultural products